Colletotrichum truncatum, an endophytic fungus derived from Musa acuminata (AAA group): antifungal activity against Aspergillus isolated from COVID-19 patients and indole-3-acetic acid (IAA) production - Yansombat, Jiraporn; Samosornsuk, Seksun; Khattiyawech, Chollanant; Hematulin, Panarat; Pharamat, Thirawatthana; Kabir, SM Lutful; Samosornsuk, Worada (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
Fungal endophyte is a fungal that lives in plant organism as mutualism association. The role of fungal endophyte is a growth promoter or/and microbial pathogen inhibitor. This study investigated antifungal activity of Colletotrichum truncatum E10, an endophytic fungus derived from Musa acuminata (AAA group), against 7 isolates of Aspergillus obtained from lower respiratory samples of COVID-19 patients. In addition, IAA production of this strain was also observed. All isolates of Aspergillus were identified using MALDI-TOF MS. The fungal endophyte, C. truncatum E10, was screened for IAA induction with and without 0.1, 2 and 8 mg/mL of L-tryptophan based on colorimetric method using Salkowski reagent which produced pinkish to reddish solution indicating the presence of IAA. Antagonist activity was based on dual culture assay measured in colony growth inhibition (CGI). C. truncatum E10 produced the highest IAA concentration of 112.81±0.12 µg/mL when 8 mg/mL of L-tryptophan added. The strong antagonist activities were shown by C. truncatum E10 against 5 Aspergillus isolates including 2 A. fumigatus: sp442/6 (CGI=57.83±5.11%) and sp269/11 (CGI=53.01±8.52%), 1 A. niger sp26/7 (CGI=57.83±15.33%) and 2 A. flavus: sp26/7 (CGI=56.63±13.63%) and sp36/7 (CGI=57.23±0.85%), whereas the colony growth inhibition (CGI) of other 2 isolates including A. fumigatus sp567/6 and A. flavus sp269/11 were less than 50%. In this study, C. truncatum E10 produced substances that inhibited human fungal pathogen including A. fumigatus, A. flavus and A. niger. Moreover, it can produce IAA activity. Further investigations are being conducted to expand the plant growth promotion effects and determine IAA biosynthesis pathway. For antifungal activity, the bioactive metabolites produced by this endophytic fungal isolate should be characterized to specify the effective compounds. Asian Australas. J. Biosci. Biotechnol. 2023, 8 (2), 23-29